Bohdan Pavlu and His Activities in Russia (1915—1919) - M. A. Vasilchenko; J. Vaculik (Научный диалог, 2021)
The article is devoted to the study of the political activity of one of the prominent figures of the Czech and Slovak national movement Bohdan Pavlu, who played a significant role in the Civil War in Russia. The material was documents of personal origin and official documents containing information on the activities of sCzech-Slovak organizations in Russia. The author pays attention to the evolution of political views of B. Pavlu, his attitude to the tsarist government. It is shown how external circumstances influenced the support of the course of T. G. Masaryk. Particular attention is paid to the activities of B. Pavlu during the Civil War in Russia. The novelty of the research is due to the fact that for the first time the socio-political views of one of the leaders of the Czech national movement in Russia are comprehensively studied. The relevance of the study is due to the lack of consensus in Russian society on the role of foreign intervention in the events of 1917—1922. It is proved that B. Pavlu’s activities contributed to the consolidation of the Czech and Slovak national movement in Russia. It is emphasized that it was he who formulated the concept of “Czechoslovakia”, which formed the basis for the idea of creating a single state for the two peoples.